Morphological destruction of cultured cells by the attachment of Treponema pallidum. Issue 1 (February 1982) - Fitzgerald, T J; Repesh, L A; Oakes, S G
Abstract : The incubation of Treponema pallidum with rabbit testicular cells, HEP-2 cells, human foreskin cells, rat cardiac cells, and rat skeletal muscle cells caused morphological disruption of these cultured cells. Control preparations of heat-inactivated treponemes, a high-speed supernatant in which treponemes had been pelleted, and culture medium failed to damage the tissue cells, as did viable treponemes when the cells were incubated in inverted Sykes-Moore chambers. Thus, cellular disruption is not associated with soluble treponemal, soluble inflammatory, or soluble testicular constituents but is mediated by the specific attachment of T pallidum. This organism apparently elaborates some type of toxic activity that lyses membranes: this may explain some of the histopathology of syphilitic disease.